Design of Lighting Control with RTC Timer and SMS Using Microcontroller - Agung, IGAP Raka; Djuni H, IGAK Diafari (Journal of Electrical, Electronics and Informatics; Vol 1 No 1 (2017): JEEI (February 2017)DO - 10.24843/JEEI.2017.v01.i01.p05, 2017)
The purpose of this research is to make the switch to turn on and off lighting with time can be set based on certain conditions. Controller utilizes Arduino UNO microcontroller with input from DS1307 RTC IC, photodiode, IComSat V1.1 with the output of LCD display and lighting switch. In this study realized photodiode sensor to detect dark and light illumination, DS1307 RTC IC as a source of real-time equal to the time actually, IComSat v1.1 SIM900 GSM/GPRS Shield for Arduino to communicate with HP via SMS, switch circuit and drivers for turn on and off the load of lighting and Arduino UNO with programs that has been put into flash memory. Research results obtained are supporting components of the equipment control to turn on and off of lighting utilizing microcontroller can be realized and are functioning in accordance with the plan. Two lightings can already turn on and off based on the input time of the RTC (the default) and on off status can be checked by SMS. Both lightings can already be turn on and off by SMS messages sent from mobile HP and received by microconroller (IComSat) and feedback lighting conditions is already accepted by mobile HP corresponds to on and off lights condition.